2018
DOI: 10.1111/1467-9566.12823
|View full text |Cite
|
Sign up to set email alerts
|

‘No one is as invested in your continued good health as you should be:’ an exploration of the post‐surgical relationships between weight‐loss surgery patients and their home bariatric clinics

Abstract: This article traces the post-surgical relationship between weight-loss surgery (WLS) patients and their home bariatric clinics. Following surgery, there is substantive drop off in patient attendance at both follow-up appointments and support groups. While barriers to follow-up are often discussed with the bariatric literature, patients themselves are typically defined as the problem. Based upon a thematic analysis of 217 blog posts and comments in two top patient-led online forums, I demonstrate that bariatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 74 publications
(102 reference statements)
0
40
0
Order By: Relevance
“…Tables 1 and 2 summarize the current state of the literature in terms of published eHealth strategies, programs and interventions specifically targeting individuals who are either undergoing or who have completed MBS by study design (review articles to randomized controlled trials) and several other key characteristics. 1461 Specifically, Tables 1 and 2 are organized by the RE-AIM constructs as follows: (1) the Reach column reports sample characteristics (e.g. unit of analysis, mean age, sex); (2) the Efficacy/Effectiveness column reports the primary focus or premise of the study; (3) the Adoption column summarizes the key reported primary and secondary (where applicable) outcomes; (4) the Implementation column reports the eHealth mechanism (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 summarize the current state of the literature in terms of published eHealth strategies, programs and interventions specifically targeting individuals who are either undergoing or who have completed MBS by study design (review articles to randomized controlled trials) and several other key characteristics. 1461 Specifically, Tables 1 and 2 are organized by the RE-AIM constructs as follows: (1) the Reach column reports sample characteristics (e.g. unit of analysis, mean age, sex); (2) the Efficacy/Effectiveness column reports the primary focus or premise of the study; (3) the Adoption column summarizes the key reported primary and secondary (where applicable) outcomes; (4) the Implementation column reports the eHealth mechanism (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 38 studies were found that met the search criteria, from years 2011 to 2019. There were a total of 16 descriptive/partial analytical studies 2035 that included six reviews, nine qualitative and one mixed methods study (Table 1). There were a total of 22 analytical studies of which six were observational/cross-sectional, nine were prospective cohort designs, four were quasi-experimental and three were randomized controlled trials (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…) but also a high prevalence of self‐reported medical, nutritional and surgical symptoms (Gribsholt et al . ) and deficient long‐term follow‐up from health professionals (Meleo‐Erwin , Torgersen et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Second and relatedly, as some authors have noted (Koball et al, 2017;Martins et al, 2015), bariatric patients may now be connecting via social media sites such as Facebook rather than websites such as OH. Nevertheless, sites like OH continue to have high traffic use and thus the conclusions drawn in this study about online WLS patient communities may still be relevant (Meleo-Erwin, 2019). Third, the sample was overwhelmingly female and based in the New York City Greater Metropolitan Area of the United States.…”
Section: Discussionmentioning
confidence: 93%